Mycobacteriophage-mediated gene transfer enables in vitro drug screening and in vivo tracking of Mycobacterium leprae - Lahari Das; Bing Chen; Saranathan Rajagopalan; Catherine Vilchèze; Claire V. Mulholland; Michael Berney; Patrick K. Andrews; Ashley Edwards; Ramanuj Lahiri; William R. Jacobs (Proceedings of the National Academy of Sciences, 2025)
Mycobacterium leprae , the causative agent of leprosy, has never been cultured in vitro, posing significant challenges for genetic manipulation and drug discovery. Current antileprosy drug screening methods relying on microscopic count, radiorespirometry, and qPCR are time consuming and require the use of radioactive elements. We demonstrate mycobacteriophage-mediated introduction of foreign DNA using the broad-host range mycobacteriophage TM4 and the application of the luciferase reporter mycobacteriophage (LRM) for drug screening. Mycobacteriophage infection of M. leprae was shown using TM4 expressing the highly sensitive BRET-nanoluciferase-based reporter, GeNL (TM4 ::GeNL ), which enables luminescence measurement for over 72 h. When M. leprae was exposed to rifampicin, dapsone, and Q203 for 24 and 48 h, followed by TM4 ::GeNL infection, the luminescence output decreased in a dose-dependent manner, establishing an in vitro two-day screening assay for drugs. We have also electroporated M. leprae with a ColE1 -integration proficient plasmid expressing GeNL and shown that the transformed leprosy bacilli could be propagated in mice footpads and detected using an in vivo imaging system (IVIS). These findings introduce powerful genetic tools for M. leprae research enabling in vivo tracking and in vitro viability testing.